Duodenal stenosis, an unusual presentation of eosinophilic gastroenteritis: a case report - Di Mari, Clelia; Pozzi, Elena; Mantegazza, Cecilia; Destro, Francesca; Meroni, Milena; Coletta, Marina; Sorge, Andrea; Pelizzo, Gloria; Zuccotti, Gian Vincenzo (Frontiers in Pediatrics, 2024)
Eosinophilic gastrointestinal diseases (EGIDs) are rare, chronic inflammatory disorders characterized by eosinophilic infiltration of the gastrointestinal tract. Symptoms and clinical presentations vary depending on the site and layer of the gastrointestinal wall infiltrated by eosinophils. Gastrointestinal obstruction is a serious, though uncommon, presentation. Management can be extremely challenging because of the rarity of the condition and the lack of robust scientific evidence. Current treatment approaches for EGIDs mainly focus on elimination diets, proton pump inhibitors and corticosteroids, which present high refractoriness rates. Novel targeted therapies are being investigated but not routinely used. Surgery should be avoided as far as possible; however, it may be the only option in gastrointestinal obstruction when long-term remission cannot be attained by any medical strategy. Herein we report the case of an adolescent boy affected by an eosinophilic gastrointestinal disease with progressive duodenal stenosis, refractory to medical therapy, who successfully benefitted from surgical management. He presented with a one-year history of gastrointestinal obstructive symptoms with feeding intolerance. After the diagnostic workup, he was diagnosed with an eosinophilic gastrointestinal disease (esophagitis and enteritis) with a duodenal involvement causing a progressive duodenal stenosis. Due to refractoriness to the conventional medical therapies and the consequent high impact on his quality of life, related both to the need for enteral nutrition and repeated hospitalizations, we decided to perform a gastro-jejunum anastomosis, which allowed us to obtain a clinical and endoscopic long-term remission. The early discussion of the case and the involvement of all experienced specialists, pediatricians and pediatric surgeons is essential.